2020
DOI: 10.1016/j.radcr.2020.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Severe duodenal thickening post image guided Irreversible Electroporation of Locally Advanced Pancreatic Cancer mimicking duodenal infarction: A case report

Abstract: A 44-year-old gentleman with stage III (T4N1M0) unresectable pancreatic adenocarcinoma at the uncinate process underwent percutaneous image guided Irreversible Electroporation (IRE). At day-1 post IRE the patient developed severe abdominal pain and had computed tomography for assessment of his symptoms. Computed tomography showed severe duodenal wall thickening with local inflammatory changes and was reported as duodenal infarction based on imaging features. Following conservative management with better pain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Several other studies have also demonstrated the enhanced efficacy when IRE was used in combination with other therapeutics [ 191 , 192 , 193 ]. Unfortunately, severe abdominal pain due to severe duodenal inflammation with wall thickening could result from IRE treatment [ 194 ].…”
Section: Locoregional Therapiesmentioning
confidence: 99%
“…Several other studies have also demonstrated the enhanced efficacy when IRE was used in combination with other therapeutics [ 191 , 192 , 193 ]. Unfortunately, severe abdominal pain due to severe duodenal inflammation with wall thickening could result from IRE treatment [ 194 ].…”
Section: Locoregional Therapiesmentioning
confidence: 99%